2018
DOI: 10.1177/0218492318810087
|View full text |Cite
|
Sign up to set email alerts
|

Age-related presentation of acute type A aortic dissection

Abstract: Background We evaluated the clinical and anatomic presentations of acute type A aortic dissection according to patient age. Methods We retrospectively reviewed 235 consecutive patients who underwent acute type A dissection repair between January 2000 and December 2014. The influence of age on anatomical and clinical presentation, surgical management in the entire cohort and also after exclusion of patients with known connective tissue disorders was assessed using logistic regression. Results Males presented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…On the other hand, Group B patients had a higher frequency of Penn Class BC presentation with greater extent of dissection with organ malperfusion in association with cardiovascular collapse. This observation concurs with the observations of other groups, Malvindi et al reported that the extension to the coronary sinus, descending thoracic aorta and abdominal aorta and the presence of an intimal tear at the level of the aortic root correlated inversely with age (16). The reason for this finding might be that younger patients are more likely to have connective tissue diseases or bicuspid aortic valve, which facilitate extension of the dissection proximally and distally.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Group B patients had a higher frequency of Penn Class BC presentation with greater extent of dissection with organ malperfusion in association with cardiovascular collapse. This observation concurs with the observations of other groups, Malvindi et al reported that the extension to the coronary sinus, descending thoracic aorta and abdominal aorta and the presence of an intimal tear at the level of the aortic root correlated inversely with age (16). The reason for this finding might be that younger patients are more likely to have connective tissue diseases or bicuspid aortic valve, which facilitate extension of the dissection proximally and distally.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that proximal and distal progression of dissection occurred more frequently in younger T(A)AD patients. Meanwhile, age was negatively correlated with the incidence of Valsalva sinus level intimal tear, which led to the choice of more radical proximal surgical repair in younger patients [ 23 ]. Morbid obesity may be associated with the worse prognostic implications of these surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Although many studies have explored the risk factors of acute AD, 4 it has been shown that the risk factors from different age groups differ. [4][5][6][7] All these results suggest that younger patients may have different characteristics than the older patients and new modalities of risk factor assessment should be introduced.…”
Section: Introductionmentioning
confidence: 99%